PELINTIRAN KEBENCIAN (HATE SPIN): Rekayasa Ketersinggungan dan Ujaran Kebencian dengan menggunakan Identitas Agama dan Etnik di Kalimantan Barat - Ismail Ruslan (Jurnal Al-Hikmah: Jurnal Dakwah, 2020)
Cases of hate speech in West Kalimantan increased from the previous year, especially in the momentum of the Democratic Party: the election of the Regional Representative Council (DPRD) of the Province, Regency and the City, the Governor and the Regent/Mayor. Actors of hate speech use social media to publish their content. In its development, related to the momentum of the elections, hate speech also uses religious and ethnic issues. At the same time, the use of politics as religion and ethnicity has become an important issue in the battle of regional heads in West Kalimantan, which is repeated every five years. Political events with religious backgrounds in other regions are also encouraging and disturbing vulnerability in the area of West Kalimantan, as is the case with the DKI Jakarta Regional Election which discusses religious and ethnic issues. These two issues have always been a magnet for politicians to gain support for local political rivalry. George (2017) discusses episodes of hostility, hatred and offense between groups in society that oppose natural responses that arise in society. However, this is the result of sophisticated campaigns made by political entrepreneurs for their strategic interests. The strategy of insulting is a double technique in political battles, this is what is called the twist of hatred (hate spinning). Indonesian people (read: West Kalimantan) must learn from several countries that discuss prolonged conflict to date.